STRATEGI PENGUATAN LITERASI GURU MELALUI PELATIHAN PENULISAN KARYA ILMIAH DI SMK KARTIKA XX-1 MAKASSAR - Zuhairoh, Faihatuz; Liana, Alin; Asrawati, Nur (Universitas Mataram, 2024)
The community empowerment activities for beginners at SMK Kartika XX-1 Makassar were motivated by the need to improve teachers' scientific literacy and the quality of scientific writing. This program aims to provide training and assistance in writing scientific papers to support teacher professionalism and competence, as well as to facilitate teachers in meeting the requirements of Teacher Professional Education Program (TPP). The methods used include intensive offline training and direct assistance by experts in scientific writing online. This training provides writing techniques, structuring, and use of references. After the implementation of the activity, there was a significant increase in the number and quality of scientific papers produced by teachers. Most teachers reported an increased understanding of the correct writing structure and reference techniques. The scientific papers produced showed an increase in professionalism and scientific relevance. Increasing teachers' scientific literacy also has a positive impact on the quality of education in schools, with more articles published and contributions to the achievement of school Key Performance Indicators (KPI). In addition, teachers feel more prepared to face challenges in the PPG program. The empowerment program has succeeded in improving teachers' scientific writing competencies, supporting their professional development, and contributing to improving the quality of education at SMK Kartika XX-1 Makassar.